Implementasi Model Problem Based Learning Berbantuan PhET Simulation untuk Meningkatkan Hasil Belajar Fisika Siswa di SMAN 2 Samarinda - Pratiwi, Distryarin Enggar; Komariyah, Laili; Damayanti, Puardmi (JURNAL PEMBELAJARAN FISIKA, 2024)
This study aims to determine the improvement of physics learning outcomes using a problem-based learning model assisted by PhET simulation media on effort and energy material. This type of research uses a quantitative approach with the Pre-Experimental Design method in the form of One-Group Pretest-Posttest. The population of this study comprised all students of class XI MIPA at SMAN 2 Samarinda, totaling 108 students, while the sample consisted of 36 students from class XI MIPA A at SMAN 2 Samarinda. Data collection was carried out using test techniques consisting of 10 essay questions given before and after treatment. This study used the N-Gain test as a statistical test. The results showed that the average pretest score was 11.33 and the average posttest score was 75.61. The category of improvement in student learning outcomes is classified as high based on the average N-Gain score of 0.73. These results indicate an increase in student learning outcomes after the treatment. Therefore, the implementation of a problem-based learning model assisted by PhET simulation can be used as an alternative to improve physics learning outcomes.